Effect of bee wax and linseed oil coatings and frequency of dipping on the biochemical and organoleptic quality of fresh orange juice (Citrus sinensis cv. Valencia) - Mezemir, Samuel; Abera, Solomon; Solomon, W K (Journal of Postharvest Technology, 2017)
An investigation was carried out to study the effects of bee wax and linseed oil coatings and frequency of application on the quality of juice  extracts during ambient storage for 28 days. It was found that the results of both wax coating and oil dipping were significantly (p < 0.05)  different from and better than that of control in many of the parameters. Fruit from BW3 (bee wax emulsion three time dip) treatment had the  lowest weight losses during storage periods. The ascorbic acid content and titratable acidity decreased while the total soluble solids and pH  increased for all treatments, the rate being significantly (p < 0.05) slower for coated samples. Linseed oil at all levels of application and  BW3treatments had significantly (P < 0.05) lower total aerobic bacteria and total mold and yeast counts than control samples on 28th day and  were able to inhibit microbial growth for 21 storage days. The color score of coated fruits was generally better than control fruits. The flavor,  generally, was reducing in acceptability as storage days increased. It can be concluded that bee wax emulsion is promising than linseed oil,  especially in three times application level, as a coating material for Valencia oranges.
Keywords: Bee wax emulsion; coating; linseed oil,; orange juice; quality.